The relationship between experiential avoidance and posttraumatic stress symptoms: A moderated mediation model involving dissociation, guilt, and gender - Serrano-Ibáñez, Elena Rocío; Ruiz-Párraga, Gema Teresa; Gómez-Pérez, Lidia; Ramírez-Maestre, María del Carmen; Esteve-Zarazaga, Rosa; López-Martínez, Alicia Eva (Taylor and Francis Group Routledge, 2021)
Experiential avoidance, dissociation, and guilt have been shown to be associated with trauma exposure and to play an important role in explaining the development and maintenance of posttraumatic stress symptoms. However, there is a lack of studies that simultaneously address the relationship between these variables, which has never been studied within the framework of emotional processing theory. Furthermore, gender differences in traumatic victimization, posttraumatic stress symptoms, experiential avoidance, dissociation, and guilt have also been reported. Therefore, this study had a double aim: a) to assess the mediating roles of dissociation and guilt in the relationship between experiential avoidance and posttraumatic stress symptoms; and b) to investigate whether gender moderates any such relationship. The final sample comprised 683 undergraduate students (150 men and 533 women) with a history of exposure to traumatic events and with posttraumatic stress symptoms. Mediation and moderated mediation analyses were conducted. Dissociation and guilt independently mediated the association between experiential avoidance and posttraumatic stress symptoms: however, this mediation effect was not moderated by gender. The findings suggest that interventions aimed at controlling psychological variables linked to PTSD (i.e. experiential avoidance, dissociation, and guilt) may be of help to both men and women.
Keywords: Estrés (Psicología); PTSD; Experiential avoidance; Dissociation; Guilt; Gender